The association between Body Surface Area (BSA) and vitamin D level among obese adolescent patients in Denpasar, Bali, Indonesia - Luh Gede Yuliadewi NS; I Gusti Lanang Sidiartha (Intisari Sains Medis, 2020)
Background: Prevalence of obesity in adolescent in Indonesia is still high. An obese adolescent is likely to stay obese into adulthood and tends to develop into cardiovascular and metabolic diseases. Obese subjects have larger body surface area and should be able to produce more vitamin D from cutaneous synthesis. This study aims to determine the prevalence of obesity in adolescent in Denpasar, determine vitamin D status among obese adolescents and obtained an association between body surface area and vitamin D levels.Methods: A descriptive observational study using a cross-sectional approach has been conducted among 51 obese adolescents in Denpasar during May to December 2018. Several variables assessed in this study were age, sex, weight, height, Body Mass Index (BMI), Body Surface Area (BSA), and vitamin D levels. Factors associated with vitamin D levels in obese adolescence were analyzed with appropriate statistical analysis. Data were analyzed using SPSS version 17 for Windows. Results: From 51 subjects, 32 (62.74%) male and 19 (37.26%) female subjects were enrolled in this study. The mean weight and height of respondents were 89.4±9.8 kg and 158.6±7.3 cm. In addition, the average Body Mass Index (BMI) and Body Surface Area (BSA) were 33.6±3.4 kg/m2 and 2.1±0.2 m2. The mean Vitamin D levels was 18.9±4.9 ng/mL with 40 subjects (78,4%) were known in a vitamin D deficiency state. There was a significant weak positive association between BSA and vitamin D levels (r=0.32; p=0,002).Conclusion: Most obese adolescents were in vitamin D deficiency with a significant weak positive association between BSA and vitamin D levels.